Is knowledge about COVID-19 associated with willingness to receive vaccine, vaccine uptake, and vaccine booster uptake in rural Malang, Indonesia? - Sujarwoto, Sujarwoto; Maharani, Asri (Frontiers in Public Health, 2023)
Background: Lack of knowledge regarding the coronavirus disease (COVID-19) and COVID-19 vaccines is a key barrier to COVID-19 vaccine uptake in low- and middle-income countries (LMICs). Aims: To examine factors associated with knowledge about COVID-19 and the association between knowledge of COVID-19, willingness to receive a COVID-19 vaccine, and vaccine uptake in Malang, Indonesia. Method: A cross-sectional study among individuals aged 15-99 years was conducted between November 2022 and January 2023. Of 10,050 potential respondents, 10,007 were able to complete the survey. Linear regression was used to examine factors associated with knowledge about COVID-19. Logistic regression was employed to examine the association of knowledge about COVID-19 with vaccine uptake. Generalised structural equation modelling (GSEM) was performed to examine whether willingness to receive a vaccine mediated the association between knowledge about COVID-19 and vaccination uptake. Findings: The percentage of respondents who reported having received at least one dose of a COVID-19 vaccine was 94.8%, while the percentage of those who reported having received at least three doses was 88.5%. These numbers are higher than the national average for COVID-19 vaccine and booster vaccine uptake. Most respondents answered about four of six knowledge items correctly (M = 4.60, SD = 1.1). Among respondents who had not received a vaccine, 83.1% expressed willingness to receive a vaccine when it became available to them. Older, more educated, employed respondents, and those with higher economic status, demonstrated more accurate knowledge about COVID-19 than younger, less educated, unemployed respondents and those with lower economic status. Respondents who demonstrated more accurate knowledge about COVID-19 were more likely to have received a vaccine (OR = 1.528, 95% CI = 1.428-1.634) and a booster vaccine (OR = 1.260, 95% CI = 1.196-1.328). Willingness to receive a vaccine mediated the association between knowledge about COVID-19 and vaccine uptake (coef. = 0.426, 95% CI = 0.379-0.473). Implications: Interventions and public health programs aiming to improve knowledge about COVID-19 can be implemented to improve individual willingness to receive COVID-19 vaccination and to improve COVID-19 vaccine uptake among the general population.